PERSYARATAN JAMINAN DAN PENYELESAIAN KREDIT MACET DALAM PRAKTEKNYA PADA LEMBAGA PERKREDITAN DESA (LPD) DESA ADAT KUTA - Wijaya Negara, I Gusti Bagus; Puspawati, I Gusti Ayu; Rudy, Dewa Gde (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 06, Juli 2013, 2013)
Collateral requirements and loan resolution in practice at Village Credit Institutions (LPD) Desa Adat Kuta has the goal to find out the condition - what conditions must exist in the granting or lending and how the shape of loan resolution in practice in LPD Desa Adat Kuta. In this study approaches the problem in use in this paper is an empirical juridical approach, by reading literature books Legislation associated with the existing problems in the field. LPD Desa Adat Kuta require collateral in obtaining loans above Rp. 2000.000,00 is to guarantee: Guarantee of Moving Object, Ownership Certificate, and Deposits LPD Desa Adat Kuta. While below Rp. 2000.000,00 the LPD Desa Adat Kuta does not require the existence of a guarantee, only just a letter of recommendation from the Kelian Adat concerned. Form of loan resolution, LPD Desa Adat Kuta in two ways, namely by way of: Non-Litigation and Litigation.
Keywords: Security Requirements, Problem Loan, Non-Litigation and Litigation